Sex-Pheromone-Mediated Mating Disruption Technology for the Oriental Fruit Moth, Grapholita molesta (Busck) (Lepidoptera: Tortricidae): Overview and Prospects - Wei N. Kong; J. Li; Ren J. Fan; Sheng C. Li; Rui Y. Ma (Psyche: A Journal of Entomology)
A great deal of progress has been made over the last three decades in research on pheromone-mediated mating disruption technology for the oriental fruit moth, Grapholita molesta (Busck). Pheromones can interrupt normal orientation, and the most likely mechanism of pheromone disruption, competitive-attraction (false-plume following), invokes competition between point sources of pheromone formulation and females for males. This technology, performed by broadcasting pheromones into orchards to disrupt mate finding, has been successfully implemented in oriental fruit moth control. Reservoir-style dispensers made of polyethylene tubes, which release pheromone throughout the full growing season, are the current industry standard. Although reasonably effective, they require labor-intensive hand application. Recently, a new formulation, paraffin wax, which maximizes competition between point sources of synthetic pheromone and feral females for males, was shown to have high disruption performance. As this formulation is highly effective, inexpensive, and easy to produce, further study and development are advisable. Increased understanding of the principles of mating disruption will aid in the design of more effective dispensers. Continued research is needed to meet grower concerns with regard to risk, efficacy, and cost and to identify other semiochemicals that can be applied to this delivery system. Greater knowledge of the integration of different biological control methods is therefore essential.